Feminist Epistemology and Philosophy of Science
XXX, 268 p.
Keywords: This collection brings together exciting new works that address today’s key challenges for a feminist power-sensitive approach to knowledge and scientific practice. Taking up such issues as the role of contextualism in epistemology, democracy and dissent in knowledge practices, and epistemic agency under conditions of oppression, the essays build upon well-established work in feminist epistemology and philosophy of science such as standpoint theory and contextual empiricism, offering new interpretations and applications. Many contributions capture the current engagement of feminist epistemologists with the insights and programs of nonfeminist epistemologists, while others focus on the intersections between feminist epistemology and other fields of feminist inquiry such as feminist ethics and metaphysics. An important resource both for students and scholars of feminist epistemology and philosophy of science, with sections of interest to social epistemologists and philosophers of science more generally, this collection represents the broad array of the feminist epistemological work now being done, and the many ways in which feminists incorporate power dynamics into their analyses. It clearly represents both the breadth and the depth of this now well-developed area of feminist scholarship.